Creative Product Innovation and Its Marketing Strategy To Advance MSMEs and Empowering Women in Talaga Village - Deris Desmawan (EQUATOR SINAR AKADEMIA, 2023)
Talaga Village has a fairly high population density with a total of 4174 inhabitants recorded at the end of 2021 and is currently entering the demographic bonus phase so it must be make the best use of it. The proportion of the female population is almost more than half of the total village population of 2054 people, combined with 213 business units facing the challenges of the digital economy, so it is a must to have Micro, Small and Medium Enterprises (MSMEs) which contribute greatly to the village economy. However, based on this number, all MSME units are still operating offline. Even though the potential of information and communication technology infrastructure has reached all village area. Therefore a strategy is needed through innovation in the development of MSMEs in this era Abstract today's massive digital economy. One of them is through E-MSMEs, namely marketing online -based MSME products as a progressive step to improve the economy Talaga Village. The stages that must be carried out include socialization as well as data collection, creation of e-commerce accounts, to goods delivery systems. This case do for facing the challenges of the digital economy, so it is a must to have Micro, Small and Medium Enterprises (MSMEs) which contribute greatly to the village economy. effective marketing strategies and policies. This method is expected to maintain existence UMKM, empower women, and improve their economy in Talaga Village.